Ras GTPase-activating proteins control neuronal circuit development in barrel cortex layer 4 - Rao, Madhura S.; Mizuno, Hiromi; Iwasato, Takuji; Mizuno, Hidenobu (Frontiers in Neuroscience, 2022)
The cerebral cortex comprises a complex and exquisite network of neuronal circuits that is formed during development. To explore the molecular mechanisms involved in cortical circuit formation, the tactile somatosensory pathway that connects the whiskers and cortex of rodents is a useful model. Here, we analyzed the roles of Ras GTPase-activating proteins (RasGAPs) in the circuit formation in the somatosensory cortex layer 4 (L4). We suppressed the function of RasGAPs in L4 neurons using Supernova RNAi, a plasmid vector-based sparse cell gene knockdown (KD) system. The results showed disrupted dendritic pattern formation of L4 spiny stellate neurons on the barrel edge by RasGAP KD. Furthermore, the number of presynaptic boutons on L4 neurons was reduced by RasGAP KD. These results demonstrate the essential roles of RasGAPs in circuit formation in the cerebral cortex and imply that developmental changes in dendrites and synapses in RasGAP KD neurons may be related to cognitive disabilities in RasGAP-deficient individuals, such as patients with neurofibromatosis type 1.